Clinical significance of nocturnal home blood pressure monitoring and nocturnal hypertension in Asia. Issue 3 (16th February 2021) - Fujiwara, Takeshi; Hoshide, Satoshi; Tomitani, Naoko; Cheng, Hao‐min; Soenarta, Arieska Ann; Turana, Yuda; Chen, Chen‐Huan; Minh, Huynh Van; Sogunuru, Guru Prasad; Tay, Jam Chin; Wang, Tzung‐Dau; Chia, Yook‐Chin; et al.
Abstract: Nocturnal home blood pressure (BP) monitoring has been used in clinical practice for ~20 years. The authors recently showed that nocturnal systolic BP (SBP) measured by a home BP monitoring (HBPM) device in a Japanese general practice population was a significant predictor of incident cardiovascular disease (CVD) events, independent of office and morning home SBP levels, and that masked nocturnal hypertension obtained by HBPM (defined as nocturnal home BP ≥ 120/70 mmHg and average morning and evening BP < 135/85 mmHg) was associated with an increased risk of CVD events compared with controlled BP (nocturnal home BP < 120/70 mmHg and average morning and evening BP < 135/85 mmHg). This evidence revealed that (a) it is feasible to use a nocturnal HBPM device for monitoring nocturnal BP levels, and (b) such a device may offer an alternative to ambulatory BP monitoring, which has been the gold standard for the measurement of nocturnal BP. However, many unresolved clinical problems remain, such as the measurement schedule and conditions for the use of nocturnal HBPM. Further investigation of the measurement of nocturnal BP using an HBPM device and assessments of the prognostic value are thus warranted. Asians are at high risk of developing nocturnal hypertension due to high salt sensitivity and salt intake, and the precise management of their nocturnal BP levels is important. Information and communication technology‐based monitoring devices are expected to facilitate the management of nocturnal hypertension in Asian populations.